An Experimental Study on Political Science Students: Impact of the Film Wag the Dog on Political Psychology - Zaky Assidiq, Ahmad; Darwin, Rizkika Lhena; Nur Zalikha, Siti (Fakultas Ilmu Sosial dan Ilmu Pemerintahan, 2024)
The mass media has considerable influence in this age of democracy. Besides providing information, political elites are often using the media as strategic tools to alter the political landscape through the use of political imagery and rhetoric. This research employs experimental quantitative methodology to examine the impact of media, specifically the film Wag the Dog, on the behavior of political science students. By adopting three indicators drawn from political psychology principles—emotions, political beliefs, and motivations for political behavior—we identified that gender and scientific background influenced the public's reaction to the media's construction of conditions. Three results were obtained from this experimental investigation: 1) The Wag the Dog film did not have a discernible impact on the emotional dimension of students; 2) its influence on the political dimension of belief was not significant; 3) its effect on the dimension of political motives of behavior was extremely dominant; and 4) variations in responses to the three dimensions were influenced by gender disparities.